Paulus Hector Mair's “De Arte Athletica” as Pre-cinematic Animation - Margaritis, Charalambos (My University, 2022)
Building on George Sifianos’ analysis of the friezes of Parthenon and Marie-Thérèse Poncet’s approach of mediaeval illustrations as forms of animated films in a pre-cinematic era, this presentation studies in a similar way the illustrations of Paulus Hector Mair’s monumental two-volume Renaissance manuscript Opus amplissimum de arte athletica (dated circa 1540). The manuscript was a compendium of techniques which Mair found in his extensive collection of Fechtbücher (German mediaeval martial art manuals). It was intended as a complete Renaissance martial arts manual and was divided in several parts, each of which provided detailed illustrations by Jörg Breu the Younger accompanied by text descriptions on how to fight using various weapons. The presentation begins by briefly discussing the historiographical issues (as pointed out by Bendazzi, Crafton and Darley) that arise when studying, through the lens of animation studies, pre-cinematic works of art which share similarities with animation (such as the subject of this study). It proposes a theoretical framework which may help overcome anachronisms and similar theoretical missteps when identifying ‘forerunners’ of animation. The presentation then discusses the first part of Mair’s book, which is composed of 120 illustrations depicting a step-by-step guide of sword fighting techniques. Mair’s fascinating story behind the compilation of this manuscript is briefly presented and this first set of images is analysed as a set of keyframes for an animated film. The way in which their presentation follows a structure similar to the one used to create movement in an animated film is shown. Following Sifianos’ process on reconstructing the hidden movement in Pathenon’s friezes, the hypothesis of this presentation is further demonstrated by a reconstruction of the in-betweens of the movement suggested by the illustrations.
Keywords: Animation; Animation history; Cinema